A Preliminary Cadaveric MRI Study of Fetal Hip Development - Liu, Zhenqing; Li, Huixian; Wang, Shuai; Wu, Qianqian; Liu, Hongsheng (Frontiers in Surgery, 2022)
Purpose: The earlier the detection of the developmental dysplasia of the hip, the better the final outcome. This study aimed to investigate the fetal hip development using magnetic resonance imaging (MRI) to alert clinicians to possible abnormal development during intrauterine life. Method: Measurements of 34 cadaver fetuses (68 hips) were obtained regarding acetabular width and depth, anterior bony acetabular index (ABAI), anterior cartilaginous acetabular index (ACAI), posterior bony acetabular index (PBAI), and posterior cartilaginous acetabular index (PCAI). The MULTTEST procedure, linear and nonlinear regression analyses, and change-point analysis were performed to assess the trends regarding the development of these indicators. Results: As fetuses developed, acetabular width and depth increased linearly, and the slope of acetabular width was larger than that of depth. Moreover, two change points during the 24th and 34th weeks of gestation were detected with regard to width. Decreases in ABAI and PBAI were also noted. ABAI demonstrated an approximately linear trend, whereas a nonlinear trend was noted for PBAI. The change point in PBAI was observed during the 36th week. ACAI and PCAI exhibited slow increases, indicating a nonlinear trend. The change points regarding ACAI were observed during the 21st and 36th weeks of gestation. The change point for PCAI was observed during the 22nd week of gestation. Conclusion: Plots of the parameters obtained via MRI examinations of cadaver fetuses across gestational age comprehensively illustrated the fetal hip development. This information has the potential to enable an early detection of abnormal hip development during intrauterine life.